Radio and X-ray study of SNRs in the Magellanic Clouds - Sasaki, Manami; et al. (1999)
We present our high-resolution radio-continuum and X-ray study of supernova remnants (SNRs) in the Magellanic Clouds (MCs). These investigations are based on Australia Telescope Compact Array (ATCA) radio-continuum and ROSAT X-ray observations. Our main aim is to study a complete sample of the MC SNRs and H II regions.